Parametric Analysis of the Stress-Strain State for the Unsupported and Supported Horizontal Underground Workings - Tiutkin, Oleksii L.; Bondarenko, Nataliia (Széchenyi István University, Hungary, 2022)
ENG: An analysis of analytical and numerical approaches to the problem of determining the stress-strain state of underground workings has been carried out. A system of parametric analysis of the stress-strain state of unsupported and supported horizontal underground workings has been developed. This system proved that to determine the stress-strain state of horizontal unsupported workings of a certain diameter, it is enough to perform one numerical calculation of a finite-element model with unit parameters, and using simple analytical formulas, extrapolate the stress-strain state of this model to all possible cases of real workings. Finite element models of underground workings were developed to justify the author’s system. A method of parametric analysis of the strained state of a supported working by using models with equivalent bending stiffness has been developed and substantiated. On its basis, it is possible to perform a numerical analysis of a finite-element model with unit parameters of the frame, selecting the equivalent modulus of elasticity.

UKR: Проведено аналіз аналітичного та чисельного підходів до проблеми визначення напружено-деформованого стану підземних виробок. Розроблено систему параметричного аналізу напружено-деформованого стану незакріплених і закріплених горизонтальних підземних виробок. Цією системою доведено, що для визначення напружено-деформованого стану горизонтальних незакріплених виробок певного діаметра достатньо виконати один чисельний розрахунок скінченно-елементної моделі з одиничними параметрами та за нескладними аналітичними формулами екстраполювати напружено-деформований стан цієї моделі для всіх можливих випадків реальної роботи. Для обґрунтування авторської системи розроблено скінченно-елементні моделі підземних виробок. Розроблено та обґрунтовано метод параметричного аналізу деформованого стану закріпленої виробки з використанням моделей з еквівалентною згинальною жорсткістю. На його основі можна виконати чисельний аналіз скінченно-елементної моделі з одиничними параметрами оправи, вибравши еквівалентний модуль пружності.
Параметричний аналіз напружено-деформованого стану незакріпленої та закріпленої горизонтальних підземних виробок
O. Tiutkin: ORCID 0000-0003-4921-4758; N. Bondarenko: ORCID 0000-0003-0804-7500
Keywords: finite element modelling; horizontal underground working; parametric analysis; rock massif; stress-strain state; скінченно-елементне моделювання; горизонтальні підземні виробки; параметричний аналіз; породний масив; напружено-деформований стан; КТІ